Low‐Frequency Brain Oscillations Track Motor Recovery in Human Stroke. Issue 6 (30th October 2019) - Bönstrup, Marlene; Krawinkel, Lutz; Schulz, Robert; Cheng, Bastian; Feldheim, Jan; Thomalla, Götz; Cohen, Leonardo G.; Gerloff, Christian
Abstract : Objective: The majority of patients with stroke survive the acute episode and live with enduring disability. Effective therapies to support recovery of motor function after stroke are yet to be developed. Key to this development is the identification of neurophysiologic signals that mark recovery and are suitable and susceptible to interventional therapies. Movement preparatory low‐frequency oscillations (LFOs) play a key role in cortical control of movement. Recent animal data point to a mechanistic role of motor cortical LFOs in stroke motor deficits and demonstrate neuromodulation intervention with therapeutic benefit. Their relevance in human stroke pathophysiology is unknown. Methods: We studied the relationship between movement‐preparatory LFOs during the performance of a visuomotor grip task and motor function in a longitudinal (<5 days, 1 and 3 months) cohort study of 33 patients with motor stroke and in 19 healthy volunteers. Results: Acute stroke–lesioned brains fail to generate the LFO signal. Whereas in healthy humans, a transient occurrence of LFOs preceded movement onset at predominantly contralateral frontoparietal motor regions, recordings in patients revealed that movement‐preparatory LFOs were substantially diminished to a level of 38% after acute stroke. LFOs progressively increased at 1 and 3 months. This re‐emergence closely tracked the recovery of motor function across several movement qualities including grip strength, fine motor skills, and synergies and was frequency band specific. Interpretation: Our results provide the first human evidence for a link between movement‐preparatory LFOs and functional recovery after stroke, promoting their relevance for movement control. These results suggest that it may be interesting to explore targeted, LFOs‐restorative brain stimulation therapy in human stroke patients. ANN NEUROL 2019;86:853–865